Concussions in young adult athletes: No effect on cerebral white matter - Hoffman, Linda J.; Mis, Rachel E.; Brough, Caroline; Ramirez, Servio; Langford, Dianne; Giovannetti, Tania; Olson, Ingrid R. (Frontiers in Human Neuroscience, 2023)
Introduction The media’s recent focus on possible negative health outcomes following sports- related concussion has increased awareness as well as anxiety among parents and athletes. However, the literature on concussion outcomes is equivocal and limited by a variety of diagnostic approaches. Methods The current study used a rigorous, open- access concussion identification method—the Ohio State University Traumatic Brain Injury Identification method (OSU TBI-ID) to identify concussion and periods of repeated, subclinical head trauma in 108 young adult athletes who also underwent a comprehensive protocol of cognitive tests, mood/anxiety questionnaires, and high-angular-resolution diffusion-weighted brain imaging to evaluate potential changes in white matter microstructure. Results Analyses showed that athletes with a history of repetitive, subclinical impacts to the head performed slightly worse on a measure of inhibitory impulse control and had more anxiety symptoms compared to those who never sustained any type of head injury but were otherwise the same as athletes with no history of concussion. Importantly, there were no group differences in cerebral white matter as measured by tract- based spatial statistics (TBSS), nor were there any associations between OSU TBI-ID measures and whole-brain principal scalars and free-water corrected scalars. Discussion Our results provide support for the hypothesis that it is not concussion per se, but repetitive head impacts that beget worse outcomes.